AROMATHERAPY AS AN ADJUVANT TREATMENT IN CANCER CARE – A DESCRIPTIVE SYSTEMATIC REVIEW - Boehm, Katja; Büssing, Arndt; Ostermann, Thomas (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
Claims of benefits of aromatherapy for cancer patients include reduced anxiety levels and relief of emotional stress, pain, muscular tension and fatigue. The objective of this paper is to provide an updated descriptive, systematic review of evidence from pre-clinical and clinical trials assessing the benefits and safety of aromatherapy for cancer patients. Literature databases such as Medline (via Ovid), the Cochrane database of systematic reviews, Cochrane Central were searched from their inception until October 2010. Only studies on cancer cells or cancer patients were included. There is no long lasting effect of aromatherapy massage, while short term improvements were reported for general well being, anxiety and depression up to 8 weeks after treatment. The reviewed studies indicate short-term effects of aromatherapy on depression, anxiety and overall wellbeing. Specifically, some clinical trials found an increase in patient-identified symptom relief, psychological wellbeing and improved sleep. Furthermore, some found a short-term improvement (up to 2 weeks after treatment) in anxiety and depression scores and better pain control. Although essential oils have generally shown minimal adverse effects, potential risks include ingesting large amounts (intentional misuse); local skin irritation, especially with prolonged skin contact; allergic contact dermatitis; and phototoxicity from reaction to sunlight (some oils). Repeated topical administration of lavender and tea tree oil was associated with reversible prepubertal gynecomastia.